Investigating the Feasibility of a Modified Quantitative Sensory Testing Approach to Profile Sensory Function and Predict Pain Outcomes Following Intrathecal Baclofen Implant Surgery in Cerebral Palsy. Issue 1 (3rd July 2019) - Barney, Chantel C; Merbler, Alyssa M; Simone, Donald A; Walk, David; Symons, Frank J
Abstract: Objectives: Intrathecal baclofen (ITB) pumps used to manage spasticity in children with cerebral palsy (CP) also improve pain outcomes for some but not all patients. The purpose of this clinical feasibility study was to explore whether a quantitative sensory testing approach could a) be modified and used to subgroup individuals into sensory profiles and b) test whether the profiles were related to postimplant pain outcomes (i.e., pain responsive or pain persistent). Subjects: A purposeful clinical sample of nine children with CP (mean age = 12.5 years, male = 56%) and complex communication needs participated. Methods: A prospective within-subject design was used to measure proxy-reported pain before and after ITB implant. Pain response status was determined by proxy-reported pain intensity change (>50% change in maximum rated intensity). A modified quantitative sensory testing (mQST) procedure was used to assess behavioral responsivity to an array of calibrated sensory (tactile/acute nociceptive) stimuli before surgery. Results: Seven individuals with presurgical pain had mQST differentiated sensory profiles in relation to ITB pain outcomes and relative to the two individuals with no pain. Presurgically, the ITB pain responsive subgroup (N = 3, maximum rated pain intensity decreased >50% after ITB implant) showed increased behavioral reactivity to an acute nociceptive stimulus and cold stimulus, whereas the ITB pain persistent subgroup (N = 4) showed reduced behavioral reactivity to cold and repeated von Frey stimulation relative to the no pain individuals. Conclusion: Implications for patient selection criteria and stratification to presurgically identify individuals with CP "at risk" for persistent postprocedure pain are discussed.